Development and evaluation of fish eDNA metabarcoding assays facilitate the detection of cryptic seahorse taxa (family: Syngnathidae). Issue 4 (19th June 2020) - Nester, Georgia M.; De Brauwer, Maarten; Koziol, Adam; West, Katrina M.; DiBattista, Joseph D.; White, Nicole E.; Power, Matthew; Heydenrych, Matthew J.; Harvey, Euan; Bunce, Michael
Abstract: Environmental DNA (eDNA) metabarcoding methods have demonstrated their potential as noninvasive techniques for the monitoring and conservation of marine fishes, including rare and endangered taxa. However, the majority of these investigations have focused on large‐bodied taxa such as sharks and sturgeons. In contrast, eDNA studies on small‐bodied cryptic taxa are much less common. As a case in point, seahorses (members of the Syngnathidae family) have never been detected by eDNA, despite the fact that globally there are 14 species classified as "Threatened" by the IUCN. Here, we critically evaluate the ability of two existing broad‐spectrum fish metabarcoding assays (MiFish and 16S Fish) and explore the efficacy of two newly designed fish metabarcoding assays (16S_FishSyn_Short and 16S_FishSyn_Long) to detect Syngnathidae amidst a wide spectrum of fish species. Furthermore, a custom Western Australian 16S rRNA fish database was created to increase the likelihood of correct taxonomic assignments. With the newly designed assays, we detected four Syngnathidae species in a targeted eDNA survey of the Perth metropolitan area (Western Australia). These detections include the seahorse species Hippocampus subelongatus and Hippocampus breviceps, which represents the first time seahorse species have been detected using eDNA. The existing MiFish and 16S Fish assays did not detect any Syngnathidae. This evaluation of all four fish metabarcoding assays reinforces the view that every PCR assay has "blind spots". In the context of complex environmental samples, no assay is universal and false negatives will occur due to a combination of PCR efficacy, primer binding, assay sensitivity, degeneracies in the primers, template competition, and amplicon length. Taken together, these data indicate that eDNA methodologies, with ongoing optimizations, will become an integral part of monitoring small‐bodied cryptic taxa such as seahorses, gobies, and blennies and can assist in mapping species' distributions and prioritizing conservation areas.